STUDI KORELASI PEMBELAJARAN KURIKULUM MERDEKA BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN KESIAPAN GURU DALAM MENGAJAR DI SEKOLAH MENENGAH ATAS NEGERI 1 TAWANGSARI - Dani Candra; Mukhlis Faturrohman (STIT Sirojul Falah Bogor, 2025)
This research aims to find out the relationship of Islamic Religious Education subjects at SMA N 1 Tawangsari to teacher readiness in teaching. SMA N 1 Tawangsari is the place where this research was conducted. Research using descriptive with Quantitative approach. Data collection techniques using questionnaires and documentation as support. Data analysis techniques use regression analysis to determine the effect of Variable (X) to Variable (Y). The method used is the correlational research method. The results showed that there was an influence between Variable (x) and Variable (Y). Because, the results obtained from the Product Moment Test are r count of 0.888 and r table value of 0.878. Criteria r count> r table. So, Ha is accepted because there is an influence between variables. Furthermore, the calculation of the coefficient is known to be the value of r square 0.888 the influence of teacher guidance on psychomotor abilities is in the high category.